If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 9) = 24 Reorder the terms: 6(9 + y) = 24 (9 * 6 + y * 6) = 24 (54 + 6y) = 24 Solving 54 + 6y = 24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 6y = 24 + -54 Combine like terms: 54 + -54 = 0 0 + 6y = 24 + -54 6y = 24 + -54 Combine like terms: 24 + -54 = -30 6y = -30 Divide each side by '6'. y = -5 Simplifying y = -5
| 110a^3b^2-55a^2b^3+77a^3b^3=0 | | 8=x/7+5 | | 2(lnx)-ln(3x-8)=ln(7x)-ln(x+6) | | 4x+8=2x+52 | | (150/5+50*3)-(420/20*6) | | 6+17y=-15+14y | | y+4=8x | | 2x^3+x^2+1=y | | 3x-18=-7x+22 | | 1*(-7)=d | | 1/3+1/4= | | 8=n/-7-5 | | 5/3*2/3 | | y-3=x-1 | | (-7)-1=t | | .33x-5=1 | | 2(2Z-2)-2(3-3Z)=2 | | -8v-7+5v=29 | | 3(8-2m)+10=32+2(-3m+1) | | -82=6v-11v-17 | | (-8)-0=t | | 2/5(5x+5x)=-20 | | x/5-2=23 | | x-3/2=x/3 | | -16x-20y=-60 | | 6=2y+54+4y | | n-5.6=0.7 | | 5x+7=10x+3-x | | 80=-5t^2-5t+180 | | 2x^2+4x-1=7x^2-7x-1 | | (-5)+3/4=y | | -2v+8=-24 |